Let's start by calculating \( f(g(x)) \) and \( g(f(x)) \) for the given functions \( f(x) = 17x \) and \( g(x) = \frac{x}{17} \).
Part 1: Find \( f(g(x)) \)
To find \( f(g(x)) \):
- Substitute \( g(x) \) into \( f(x) \): \[ g(x) = \frac{x}{17} \] Then, \[ f(g(x)) = f\left(\frac{x}{17}\right) = 17\left(\frac{x}{17}\right) \]
- Simplify: \[ f\left(\frac{x}{17}\right) = 17 \cdot \frac{x}{17} = x \]
Thus,
\[
\boxed{x}
\]
Part 2: Find \( g(f(x)) \)
To find \( g(f(x)) \):
- Substitute \( f(x) \) into \( g(x) \): \[ f(x) = 17x \] Then, \[ g(f(x)) = g(17x) = \frac{17x}{17} \]
- Simplify: \[ g(17x) = 17x \cdot \frac{1}{17} = x \]
Thus,
\[
\boxed{x}
\]
Part 3: Determine if \( f \) and \( g \) are inverses
Since we have found:
- \( f(g(x)) = x \)
- \( g(f(x)) = x \)
This shows that: \[ f(g(x)) = x \quad \text{and} \quad g(f(x)) = x \]
Therefore, \( f \) and \( g \) are inverses of each other.
Thus, the answer is:
\[
\text{f and g are inverses of each other.}
\]
You can conclude with:
\[
\text{f and g are inverses of each other.}
\]